2019
DOI: 10.24329/aspikom.v4i1.385
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Terpaan Media Terhadap Partisipasi Politik Dalam Pilkada Dki Jakarta 2017

Abstract: The political participation of the people is one of the indicators of democracy in every country. More and more citizens are involved the better, as it shows citizens following and understanding the political problems. This study uses the Stimulus-Response (S-R) theory. The purpose of this study is to examine whether the hypothesis that there is a positive and significant influence between media exposure to the level of political participation among the people of South Jakarta. This research used quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…In addition to climate change, land use changes are the cause of tidal flooding in coastal areas. Halim [21] stated that land use change has a correlation with the magnitude of flood discharge, especially in downstream areas. Generally, abrasion occurs in coastal areas where mangrove forests have been depleted.…”
Section: B Aspect Of Technical Barriermentioning
confidence: 99%
“…In addition to climate change, land use changes are the cause of tidal flooding in coastal areas. Halim [21] stated that land use change has a correlation with the magnitude of flood discharge, especially in downstream areas. Generally, abrasion occurs in coastal areas where mangrove forests have been depleted.…”
Section: B Aspect Of Technical Barriermentioning
confidence: 99%
“…When viewed from several studies on flood discharge in various watersheds, it is revealed that several factors play a role, including geomorphology, hydroclimatology and hydrogeology [14] . More specific factors are the amount of rainfall, the area of the catchment area, the area of land cover, the type of soil or rock and topography [15] . The Kayan River Basin is located in a tropical rain forest area with high rainfall intensity.…”
Section: Maximum Daily Rainfall and Estimated Flood Dischargementioning
confidence: 99%
“…After the 2014 General Election, 2017 Governor Election in Greater Jakarta also being marked as one of the significant roles of social media when observing political participation in Indonesia with a low level of online participation in the strategic level. It means even though the engagement in using social media is high, the capability to use it as a tool to develop political knowledge is still low (Halim & Jauhari, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 99%